Antinociceptive effects of alkaloids rich fraction of aidia densiflora in mice - Soib, Husnul Hanani; Wan Sulaiman, Wan Mohd. Azizi; Darnis, Deny Susanti; Tg Zakaria, Tg Muhammad Faris Syafiq; Edueng, Khadijah; Bakhtiar, M. Taher (Malaysian Pharmaceutical Society, 2014)
Pain sensation is the major problem worldwide which may affect human health and lifestyle. The search for pain relieving agents continued to rise over time. Alkaloid is believed to stimulate analgesic activity via blocking transmission of pain stimuli on both central and peripheral pain. The study aimed to investigate the antinociceptive effects of alkaloids rich fraction of Aidia densiflora (AD) in albino ICR mice via acetic acid-induced writhing and the hot plate tests, which was reversed by aspirin. Four groups of mice were separated and treated with alkaloids extract from AD at increasing doses of 100, 200, 500, 1000 mg/kg. In writhing test, subcutaneously administered AD extract was reported to maximally block abdominal contraction by 71.1% at 1000 mg/kg (p<0.05) as compared to lower doses. Meanwhile, the hot plate test (55°C) revealed that intraperitoneally administered AD showed that there was no significant difference between lower doses which corresponded to 100 and 200 mg/kg AD. However, higher dose of 500 and 1000 mg/kg were statistically significant (p<0.05). Therefore, the results suggested that the alkaloid extract possessed potential analgesic activities which demonstrated to act through both peripheral and central mechanisms of pain. Despite safety and effectiveness profile of the extract, the present data may serve as the basis for the rational utilization of AD in alleviating symptoms including pain.